The relationship between the BMI‐adjusted weight loss grading system and quality of life in patients with incurable cancer. Issue 1 (6th November 2019) - Daly, Louise; Dolan, Ross; Power, Derek; Ní Bhuachalla, Éadaoin; Sim, Wei; Fallon, Marie; Cushen, Samantha; Simmons, Claribel; McMillan, Donald C.; Laird, Barry J.; Ryan, Aoife
Abstract: Background: Weight loss (WL) has long been recognized as an important factor associated with reduced quality of life (QoL) and reduced survival in patients with cancer. The body mass index (BMI)‐adjusted weight loss grading system (WLGS) has been shown to be associated with reduced survival. However, its impact on QoL has not been established. The aim of this study was to assess the relationship between this WLGS and QoL in patients with advanced cancer. Methods: A biobank analysis was undertaken of adult patients with advanced cancer. Data collected included patient demographics, Eastern Cooperative Oncology Group performance status, and anthropometric parameters (BMI and %WL). Patients were categorized according to the BMI‐adjusted WLGS into one of five distinct WL grades (grades 0–4). QoL was collected using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire‐C30. The Kruskal–Wallis test and multivariate logistic regression analyses were used to assess the relationship between the WLGS and QoL scores. Overall survival was assessed using Kaplan–Meier curve and Cox proportional hazard models. Results: A total of 1027 patients were assessed (51% male, median age: 66 years). Gastrointestinal cancer was most prevalent (40%), and 87% of patients had metastatic disease. Half (58%) of patients had a WL grade of 0–1, while 12%, 20%, and 10% had WL grades of 2, 3, and 4, respectively. Increasing WL grades were significantly associated with poorer QoL functioning and symptoms scales (all P < 0.05). Physical, role, and emotional functioning decreased by a median of >20 points between WL grade 0 and WL grade 4, while appetite loss, pain, dyspnoea, and fatigue increased by a median score >20 points, indicative of a large clinical significant difference. Increasing WL grades were associated with deteriorating QoL summary score. WL grades 2, 3, and 4 were independently associated with a QoL summary score below the median (<77.7) [odds ratio (OR) 1.69, P = 0.034; OR 2.06, P = 0.001; OR 4.29, P < 0.001, respectively]. WL grades 3 and 4 were independently associated with reduced overall survival [hazard ratio 1.54 (95% confidence interval: 1.22–1.93), P < 0.001 and hazard ratio 1.87 (95% confidence interval: 1.42–2.45), P < 0.001, respectively]. Conclusions: Our findings support that the WLGS is useful in identifying patients at risk of poor QoL that deteriorates with increasing WL grades. WL grade 4 is independently associated with a particularly worse prognosis and increased symptom burden. Identification and early referral to palliative care services may benefit these patients.